2004
DOI: 10.1089/108076804773710821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyaluronan on Free-Radical Formation, Corneal Endothelium Damage, and Inflammation Parameters After Phacoemulsification in Rabbits

Abstract: Free-radical formation may play a role in postoperative complications of phacoemulsification (e.g., corneal endothelium damage from mechanical injury). The present experiments were aimed at investigating whether different molecular weight ranges (2000-2600, 2600-3200, or 3200-3800 kDa) of hyaluronan may influence free radical formation, corneal endothelium damage, and inflammation parameters after phacoemulsification in the rabbit eye. The viscoelastic substance was injected in the anterior chamber of rabbits'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…Augustin and Dick 16 measured lipid peroxides as a marker of oxidative tissue damage in the aqueous humor after phacoemulsification in humans and demonstrated lipid peroxide levels were well correlated with the duration of the phacoemulsification. Camillieri et al 17 documented the effectiveness of hyaluronic acid in reducing free radical production and inflammatory parameters in the aqueous humor after phacoemulsification in rabbits. These results indicate that phacoemulsification is an oxidative insult to the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Augustin and Dick 16 measured lipid peroxides as a marker of oxidative tissue damage in the aqueous humor after phacoemulsification in humans and demonstrated lipid peroxide levels were well correlated with the duration of the phacoemulsification. Camillieri et al 17 documented the effectiveness of hyaluronic acid in reducing free radical production and inflammatory parameters in the aqueous humor after phacoemulsification in rabbits. These results indicate that phacoemulsification is an oxidative insult to the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, there are some recent studies that have shown that the phacoemulsification-associated endothelial injury may be caused by free radicals. [6][7][8][9] Based on these findings, it seems likely that the corneal endothelium can be damaged by free radicals during phacoemulsification because free radical species, hydroxyl radicals in particular, are highly reactive and can cause lethal injuries to cells. 10 The purpose of this study was to investigate the effects of free radicals on the corneal endothelium with special emphasis on histologic and immunohistochemical analyses after performing ultrasound oscillation in the anterior chambers of rabbit eyes.…”
mentioning
confidence: 99%
“…It has also been demonstrated that hyaluronate in anterior chamber during phacoemulsification has a pivotal role in controlling the inflammation, possibly on account of its preventing action in the formation of free radicals. 50 Based on the results of Cejková et al, 51 which point out that reactive nitrogen species are involved in the pathogenesis or selfpropagation of autoimmune dry eye syndrome, it could be hypothesized that hyaluronan might be the most appropriate molecule when the use of a lubricant is mandatory.…”
Section: Discussionmentioning
confidence: 99%